An Introduction to the special issue on computational techniques for trading systems, time series forecasting, stock market modeling, financial assets modeling - Hájek, Petr; Neri, Filippo (World Scientific and Engineering Academy and Society (WSEAS), 2013)
The aim of the special Issue Computational Techniques for Trading Systems, Time Series Forecasting, Stock Market Modeling, Financial Assets Modeling is to present some of the latest research carried out in the field of computational finance.
Úvod do speciální čísla o výpočetních technikách pro systémy pro obchodování, predikce časových řad, modelování akciového trhu, modelování finančních aktiv
Keywords: computational techniques; trading systems; time series forecasting; stock market modeling; financial assets modeling; obchodování; predikce časových řad; modelování; akciový trh; finanční aktiva